Poly ADP-ribose polymerase (PARP) inhibitors - new therapeutic strategies in Acute Myeloid Leukemia: a literature review - Nowicka, Emilia; Obel, Michał; Panuciak, Kinga; Mastalerczyk, Angelika; Czyżak, Kamila; Lejman, Jan; Makowska, Karolina; Wiśniewski, Wiktor (Journal of Education, Health and Sport, 2022)
The use of poly (ADP-ribose) polymerase (PARP) inhibitors has recently increased as a result of demonstrating their superior efficacy compared to traditional chemotherapy in various cancer subtypes in many preclinical studies and clinical trials. A better understanding of the molecular mechanisms of PARP and their underlying foci that can be used as screening markers for potential new therapeutic options would aid rational treatment strategies and improve long-term patient outcomes. The available data on acute leukemia suggest potential windows for effective treatment of PARPi in disease subgroups. In this review, we summarize the current advances in the most common PARP-based adjuvant therapies and combination strategies for the treatment of acute leukemia and discuss the future prospects and challenges of therapy with PARP inhibitors. We also discuss reports describing an increased risk of cancer treatment in patients receiving PARP inhibitors for solid tumors. The research material were publications, the search was carried out using a combination of keywords such as: "PARP inhibitor", "acute leukemia", "therapy", "PARP clinical trials". The first step was to find relevant publications from the last 15 years. The second step was to review the publications found. Studies have shown that PARP inhibitors play an increasing role in the treatment of leukemia. In addition, focusing research efforts on identifying the most effective drug combinations and sequences could help to further shape the role of PARPi in the treatment of acute myeloid leukemia (AML).